Preface - Yücel Caymaz, Gokcen Firdevs (Street Art & Urban Creativity, 2022)
The issue focuses on philosophies and designs that shape our cities on a broader scale; exploring different approaches between architecture, built environment, and nature; from material to medicinal plants, from plant scale to urban and social sciences. The issue examines the natural and built environment in Istanbul through the relationship between urban planning, urban space, architecture, and landscape architecture. It focuses on designs made in different parts of Istanbul between natural areas and built areas in the city.